THE ROLE OF THE TEACHER IN TEACHING FOREIGN LANGUAGE TO DIFFERENT AGES - Akbarova Iroda Akramovna (Web of Journals Publishing, 2024)
This article is about the role of the teacher in teaching foreign languages to different ages who want to speak a foreign language (English), and it is important to allow those who learn the language, as well as student-young people, it is important to form skills to allow them to think correctly, to listen to them even if they make a wrong statement, as well as to give their mistakes as feedback to themselves.
Keywords: foreign languages, cartoons, fairy tales, vocabulary, modern technology, methodology, overcoming fear, trust, peer-to-peer practice, solution.